A general strategy for improving the thermal insulation performance of aerogels by multiple impregnation. (October 2017) - Lei, Yaofei; Chen, Xiaohong; Hu, Zijun; Song, Huaihe; Cao, Bin
Abstract: A new strategy is proposed to make aerogels possessing both low thermal conductivity and high density by a multiple impregnation approach to the as-prepared silica aerogel monoliths using hydrolyzed sol. The result demonstrates that the thermal conductivity of aerogels after multiple impregnations does not increase compared with that of pristine aerogels and presents a minor decrease from 0.0090 to 0.0081 W/(mK) with the density increment from 0.074 to 0.218 g/cm 3 . A mechanism has been revealed that the decrease of macropores by multiple impregnation approach could be beneficial for improving the thermal insulation performance of silica aerogels in wide density range. Graphical abstract: